Answer:
Point-slope form: (y + 9) = -2(x +3)
Slope-intercept form: y = -2x - 15
Explanation:
It is important to know the formula for both point-slope (y - y,) = m(x - x,) and slope-intercept form (y = mx +b). In both cases 'm' represents the slope. In the question, slope = -2 and the point (-3, -9) is given which is the (x, y) values. We can first complete the point-slope form by plugging in the given values: (y - (-9)) = -2(x- (-3)) this can then be simplified to: (y + 9) = -2(x +3). However, in order to complete the slope-intercept form, we need to fill in the m, x and y variables and solve for 'b': -9 = -2(-3) + b or -9 = 6 + b, we then subtract 6 from both sides: -9 - 6 = 6 - 6 + b to get -15 = b. We then place our slope and y-intercept into the equation: y = -2x - 15.